2014
DOI: 10.1177/1043659614524246
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Spoken Knowledge in Low Literacy in Diabetes Scale for Use With Mexican Americans

Abstract: Purpose This article evaluates the Spoken Knowledge in Low Literacy in Diabetes (SKILLD) questionnaire, a measure of essential knowledge for type 2 diabetes self-management, after it was modified for English- and Spanish-speaking Mexican Americans. Method We collected surveys (SKILLD, demographic, acculturation) and blood for A1C analysis from 72 community-recruited participants to analyze the SKILLD’s internal consistency, interrater reliability, item analysis, and construct validity. Clinical experts evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 18 publications
1
15
3
1
Order By: Relevance
“…Many participants in this study instead reported the signs and symptoms of hypoglycemia, unrelated symptoms, or stated "I don't know." This finding was similar to that reported in other studies with Hispanics in the US, 15,22 mixed racial and ethnic groups in the US, 18 and Brazilians. 21 Misinterpreting the signs and symptoms of hypoglycemia versus hyperglycemia may potentially cause harm because the treatment options are significantly different.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Many participants in this study instead reported the signs and symptoms of hypoglycemia, unrelated symptoms, or stated "I don't know." This finding was similar to that reported in other studies with Hispanics in the US, 15,22 mixed racial and ethnic groups in the US, 18 and Brazilians. 21 Misinterpreting the signs and symptoms of hypoglycemia versus hyperglycemia may potentially cause harm because the treatment options are significantly different.…”
Section: Discussionsupporting
confidence: 92%
“…The finding is consistent with the NHANES study that Mexican Americans had the lowest knowledge of A1C, blood pressure, and LDL cholesterol. 14 Garcia et al 22 and Peña-Purcell and Boggess 15 similarly found that Hispanics with diabetes had low knowledge of A1C levels, although higher than this current study. The latter study reported high levels of knowledge related to fasting blood glucose.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…[28] As previous investigations have reported poor glycaemic control among diabetic patients, it is necessary that physicians pay greater attention to illiterate patients and bring to bear more patience in their education with a view to attaining favourable treatment results. [30]…”
Section: Discussionmentioning
confidence: 99%